The Ventrolateral Periaqueductal Gray Contributes to Depressive-Like Behaviors in Recovery of Inflammatory Bowel Disease Rat Model - Ko, Chih-Yuan; Yang, Ya-Bi; Chou, Dylan; Xu, Jian-Hua (Frontiers in Neuroscience, 2020)
Background: Patients with inflammatory bowel disease (IBD) experience depression, even in the remission phase of IBD symptoms. Although mapping depression-associated brain regions through the gut-brain axis can contribute to understanding the process, the mechanisms remain unclear. Our previous results support the idea that glutamatergic transmission in the ventrolateral periaqueductal gray (vlPAG) mediates stress-induced depression-like behaviors. Thus, we hypothesize that the vlPAG plays a role in regulating depression during remission of IBD. Methods: We used dextran sulfate sodium (DSS)-induced visceral pain model to evoke depression-like behaviors, assessed by tail suspension test and sucrose preference test, and electrophysiological recordings from vlPAG. Results: Symptoms of animals modeling IBD were relieved by replacing DSS solution with normal drinking water, but their depression-like behaviors sustained. Moreover, the impairment of glutamatergic neurotransmission in vlPAG was sustained as well. Pharmacologically, microinfusion of the glutamate receptor 1 antagonist NASPM into vlPAG mimicked the depression-like behaviors. Furthermore, intra-vlPAG application of AMPA and AMPA receptor-mediated antidepressant (2R,6R)-hydroxynorketamine reversed the DSS-induced depression-like behaviors in the remission phase of visceral abnormalities. Conclusion: Our results suggest that vlPAG glutamatergic transmission mediates depression-like behaviors during remission of DSS-induced visceral pain, suggesting that vlPAG mapping to the gut-brain axis contributes to depression during remission of IBD.